2021
DOI: 10.1155/2021/4487988
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Preoperative Serum Carcinoembryonic Antigen Varies with Lymph Node Metastasis Status in Colorectal Cancer

Abstract: Background. Preoperative serum level of carcinoembryonic antigen (pCEA) is generally recognized as a prognostic factor for colorectal cancer (CRC), but the stage-specific role of pCEA in colorectal cancer remains unclear. Objective. We investigated the prognostic significance of pCEA levels in different tumor stages of nonmetastatic CRC patients. Methods. Six hundred and fifteen CRC patients at stage I–III were retrospectively analyzed. All of them received curative tumor resection. The X-tile program was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…By multivariate analyses, elevated baseline level of CA19-9, advanced pN stage and harvested lymph nodes less than 12 were found to be independently associated with DM, and the first two were also independent prognostic factors for DFS, whereas advanced pN stage was associated with poor CSS. It is known that many tumor markers, such as CEA and CA19-9, are useful prognostic indicator to predict relapse and survival in rectal cancer patients (23)(24)(25). In addition to the association between baseline CA19-9 level and DM after laparoscopic resection of rectal cancer, our study showed that elevated baseline level of CEA was an independent risk factor for lung metastasis and predicted inferior DFS.…”
Section: Discussionsupporting
confidence: 56%
“…By multivariate analyses, elevated baseline level of CA19-9, advanced pN stage and harvested lymph nodes less than 12 were found to be independently associated with DM, and the first two were also independent prognostic factors for DFS, whereas advanced pN stage was associated with poor CSS. It is known that many tumor markers, such as CEA and CA19-9, are useful prognostic indicator to predict relapse and survival in rectal cancer patients (23)(24)(25). In addition to the association between baseline CA19-9 level and DM after laparoscopic resection of rectal cancer, our study showed that elevated baseline level of CEA was an independent risk factor for lung metastasis and predicted inferior DFS.…”
Section: Discussionsupporting
confidence: 56%
“…CEA is a tumor marker in gastrointestinal cancers, particularly CRC. It is used in the diagnosis, follow-up, and prognosis of CRC [ 22 ]. CEA and CA19-9 are monoclonal antibodies employed as serum markers for numerous diseases, including pancreatic, gastric, lung, biliary tract, colorectal, and other cancers [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%